A comprehensive VISIR bibliographical reference - Silva, Mariana Miguel (2022)
VISIR (Virtual Instrument Systems in Reality) is a remote laboratory environment in use in research and academic institutions since 2001. This paper presents a comprehensive VISIR bibliographical reference, including a performance analysis, which reviews the publication data and the citation indexes, and a science mapping, that presents the cognitive structure. The procedure to retrieve, aggregate, process, and analyze data is based on documented sources and is also presented in the article, including some comments on specific issues faced while applying the proposed methodology. The paper characterizes the publication evolution over time, the most prolific authors and their networks, the main research topics, the most frequent sources, and the most cited documents. The available results show a mature and evolving collaborative network and an expansion trend that allows predicting that VISIR is not only the source of many academic and applied research publications, but also a popular and continuously developing remote laboratory and the basis of a very active community.